2012
DOI: 10.14712/23362936.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Floating Norms for Czech Adults

Abstract: Key words: Lateral cephalograms -Cephalometric norms -Hasund harmony schemaAbstract: The purpose of this study was to establish floating cephalometric norms for the description of the individual skeletal pattern in Czech adults. Floating norms provide a method of analysis that uses the variability of the associations among suitable cephalometric measures, on the basis of the regression model combining both sagittal and vertical skeletal parameters. Harmony box is a simple and useful tool for diagnostics of ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Generally, the smaller the cranial angle, the more prognathic and converse the face is 17 . The above-mentioned results are confirmed in our and other studies 10,25 . If the five variables follow one of the harmonious combinations, the patient's face is considered harmonious and orthognathic.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Generally, the smaller the cranial angle, the more prognathic and converse the face is 17 . The above-mentioned results are confirmed in our and other studies 10,25 . If the five variables follow one of the harmonious combinations, the patient's face is considered harmonious and orthognathic.…”
Section: Discussionsupporting
confidence: 92%
“…The comparison of our results with those from the stud-ies by Sevilla-Naranjilla and Rudzki-Janson 10 and Řeháček et al 25 is shown in Figure 8, and variables' mean values of Filipino and Czech populations are drawn in our harmonious box and harmonious schema. For abbreviations, see under Table 1.…”
Section: Variablesmentioning
confidence: 58%
See 2 more Smart Citations
“…In this study, the data pool reflects a contemporary Central European population compared to previous investigations of Panagiotidis and Witt [17] and Järvinen [13]. In the past, several authors found (minor) differences in cephalometric values or craniofacial patterns in terms of population [5,6,18,22,25]. In addition, since the original regression formula for the individualised Wits appraisal of Järvinen [13] considered subjects with all Angle classes, we could increase its precision and validity by taking into account only subjects with class I occlusion.…”
Section: Discussionmentioning
confidence: 99%